Quantification of circulating house dust mite‐specific IL‐4‐ and IL‐13‐secreting T cells correlates with rhinitis severity in asthmatic children and varies with the seasons. Issue 2 (22nd January 2014) - Michaud, B.; Gouvis‐Echraghi, R.; Candon, S.; Couderc, R.; Jais, J. P.; Bach, J. F.; Chatenoud, L.; Just, J.
Summary Background Defining suitable markers to diagnose and monitor allergy and its severity is essential to correctly assign patients for specific immunotherapy. Circulating levels of specific IgE are good markers of sensitization, but not of clinically symptomatic allergy. Objective To quantify circulating interleukin (IL)‐4‐ and IL‐13‐secreting T cells specific for house dust mite (HDM) in children presenting HDM‐allergic asthma associated or not with rhinitis and correlate results with clinical symptoms. Methods We analysed 26 children with HDM respiratory disease (allergic rhinitis and asthma) together with six children with non‐allergic asthma. Peripheral blood mononuclear cells were stimulated with HDM extract in a 24‐h ELISpot assay to quantify the number of HDM‐specific IL‐4‐ and IL‐13‐secreting T cells. Asthma severity and control, and rhinitis severity were scored according to the Global Initiative for Asthma (GINA) and the Allergic Rhinitis and its Impact on Asthma (ARIA) Guidelines. Results The number of HDM‐specific IL‐4‐ and IL‐13‐secreting T cells was higher in patients with allergic asthma as compared to patients with non‐allergic asthma. It varied with the season of blood sampling with two peaks in the fall and early spring. Independently of the season, the number of HDM‐specific IL‐4‐secreting T cells correlated with rhinitis severity (OR = 2; 95% IC:1.1–3.8; P = 0.04). Conclusions and Clinical relevance Allergen‐specific IL‐4‐ and IL‐13‐producing T cells were only detected in HDM‐allergic asthmatic children (not in patients with non‐allergic asthma). Their numbers correlated with clinical severity of allergic rhinitis.